Sjögren Syndrome and Mucous Membrane Pemphigoid in a Patient with a History of Thymoma: Case Report and Literature Review - Boza Oreamuno DDS, MSc, Yadira V.; Evans Tinoco DMD, OPH, Mónica; Guillén Colombari DMD, Path, Diego; Torres Labardini DDS, OMS, Ronald (Odovtos - International Journal of Dental Sciences, 2019)
Thymomas are the most common mediastinal neoplasms in adults. Patients with thymoma are frequently diagnosed with paraneoplastic syndromes and are generally associated with several autoimmune conditions. Sjögren's syndrome (SS) is an autoimmune inflammatory disorder, characterized by the lymphocyte-mediated destruction of the exocrine glands, which leads to the absence of glandular secretion, particularly salivary and lacrimal; hyposalivation can vary from a slight reduction in the flow of saliva with transient discomfort, to a serious deterioration of oral health and psychological distress. Mucous membrane pemphigoid (MMP) is a chronic, autoimmune disease that shows predominant mucosal involvement, most commonly affecting the oral cavity, followed by the conjunctiva, the nasal cavity and the esophagus; intraorally includes scaly gingivitis, vesicles, erosions covered by pseudomembranes and ulcers. The objective of this work is to present the first case of a patient with a history of thymoma, which, jointly presented SS and MMP; also highlight the importance of multidisciplinary management for an accurate and early diagnosis, as this increases the efficiency and efficacy of the treatment strategy.